The right side of this equation: can be rewritten as: . Then, can be written as , where and are positive coprime integers. Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The (x-a)^b/c is (x-1)^3/2 which is equal to 8 on simplifying we get x=5. therefore (2x+c)/(3b-a)=12/8=3/2=m/n and m+n=5.